Supramolecular architectures featuring Se···N secondary-bonding interactions in crystals of selenium-rich molecules: A comparison with their congeners. - Tiekink, Edward R. T. * (Royal Society of Chemistry, 2022)
Supramolecular aggregates featuring Se···N contacts have been identified in 88 crystals containing, two, three or four selenium atoms, corresponding to 9% of crystals where Se···N contacts have the potential to form. Molecules with two selenium atoms make up the majority of examples (58) followed by molecules with three (12) and four (18) selenium atoms. A wide range of supramolecular aggregation patterns have been identified in the 88 crystals featuring Se···N contacts with one- (42%) and two- (31%) dimensional aggregation forming the majority compared with zero- (17%) and three- (10%) dimensional aggregation making up the rest. The overwhelming majority of Se···N contacts correspond to chalcogen-bonding interactions based on σ-hole interactions. Correlations in intermolecular separations were evident for isostructural crystals showed a comparable Te···N interaction was stronger than the equivalent Se···N interaction, and the Se···N interaction was always stronger than the equivalent S···N interaction. When compared to crystals of mono-nuclear selenium compounds, a very similar 2 adoption rate was observed in their crystals but with a bias towards smaller aggregations patterns, i.e. 50, 44, 5 and 1% for zero-, one-, two- and three- dimensional, respectively. This observation is clearly consistent with the greater opportunity for multi-nuclear selenium molecules to form more interactions. However, as exemplified by the 18 tetra-nuclear molecules, not all selenium atoms participated in a Se···N contact as two, 10, two and four selenium atoms, out of a possible four, formed a Se···N contact in their crystals.